Dedicatory Epistles to the King in Matters of Faith in the Polish Protestant Bibles in the 16th and 17th Century - Meller, Katarzyna (Poznańskie Studia Slawistyczne, 2016)
The article examines religious topics in dedicatory letters for the Polish Protestant Bibles of the 16th and 17th century. The New Testament published by Jan Seklucjan (1551–1553), the Brest Bible (1563) and the Gdansk Bible (1632) were dedicated to the reigning kings towards whom the Protestants expressed their expectations about the place of the Church / religion in the state and the role of the ruler. The dedicatory letters by Seklucjan, Mikolaj Radziwill and Krzysztof Radziwill highlighted the concept of the primacy of secular authority over the Church, namely, the sovereignty of the monarch, personifying the majesty and law of the Republic over the Church of God, i.e. people who constitute the community of faith. According to the Polish political status, king, due to his office, played the role of the “servant of the Republic”, and as the guardian of the legal order, was not to be the ruler of conscience, but the guardian of freedom of speech and religion.